Chemotherapeutic Agent-induced Nephrotoxicity in Rabbits: Protective Role of Grape Seed Extract - Benzer, Fulya; Kandemir, Fatih Mehmet; Ceribasi, Songul; Ozkaraca, Mustafa; Yildirim, Nuran Cikcikoglu; Ozan, Sema Temizer (Asian Network Scientific Information-Ansinet, 2012)
Cisplatin (CP) is one of the most effective cancer chemotherapeutic agent used against various solid tumors. This study was designed to investigate the antioxidant effects of Grape Seed Extract (GSE) on CP induced oxidative damage in rabbit kidney. The material of study was consist of 18 male New Zealand rabbit. Animals were divided into 3 groups. The first group was administered a single intraperitoneal (i.p.) close of 0.9% saline. The second group of rabbits was treated with CP (a single i.p. dose of 5 mg kg(-1) body weight); The third group of rabbits was treated with GSE by gavage at the dose of 250 mg kg(-1) body weight for 6 consecutive days before and 6 consecutive days after a single i.p. CP injection. As a result of CP administration, kidney function tests; urea, BUN (Blood Urea Nitrogen) and creatinine levels were increased (p<0.001). It was observed that CP increase malondialdehide (MDA) levels, the most important indicator of oxidative damage and decreased the activity of catalasc (CAT). Administration of CP did not caused statically a change in glutathione (GSH) levels and glutathione peroxidase (GSH-P-x) activity (p>0.05). GSE treatment has high levels of MDA to compared to normal levels (p<0.001) but not an increase in CAT (p<0.05). In CP treatment group, severe acute tubular necrosis was seen. It was determined that in CP+GSE group mild degenerative changes were received instead of acute tubular necrosis. GSE has been found to be partially protective effect against CP induced biochemical and histopathological changes in rabbit kidney.
Keywords: Cisplatin; grape seed extract; nephrotoxicity; rabbit